Antimicrobial Activities of Aztreonam-Avibactam and Comparator Agents against Enterobacterales Analyzed by ICU and Non-ICU Wards, Infection Sources, and Geographic Regions: ATLAS Program 2016-2020 - Denis Piérard; Elizabeth D. Hermsen; Michal Kantecki; Francis F. Arhin (MDPI AG, 2023)
Increasing antimicrobial resistance among multidrug-resistant (MDR), extended-spectrum β-lactamase (ESBL)- and carbapenemase-producing Enterobacterales (CPE), in particular metallo-β-lactamase (MBL)-positive strains, has led to limited treatment options in these isolates. This study evaluated the activity of aztreonam-avibactam (ATM-AVI) and comparator antimicrobials against Enterobacterales isolates and key resistance phenotypes stratified by wards, infection sources and geographic regions as part of the ATLAS program between 2016 and 2020. Minimum inhibitory concentrations (MICs) were determined per Clinical and Laboratory Standards Institute (CLSI) guidelines. The susceptibility of antimicrobials were interpreted using CLSI and European Committee on Antimicrobial Susceptibility Testing (EUCAST) breakpoints. A tentative pharmacokinetic/pharmacodynamic breakpoint of 8 µg/mL was considered for ATM-AVI activity. ATM-AVI inhibited ≥99.2% of Enterobacterales isolates across wards and ≥99.7% isolates across infection sources globally and in all regions at ≤8 µg/mL. For resistance phenotypes, ATM-AVI demonstrated sustained activity across wards and infection sources by inhibiting ≥98.5% and ≥99.1% of multidrug-resistant (MDR) isolates, ≥98.6% and ≥99.1% of ESBL-positive isolates, ≥96.8% and ≥90.9% of carbapenem-resistant (CR) isolates, and ≥96.8% and ≥97.4% of MBL-positive isolates, respectively, at ≤8 µg/mL globally and across regions. Overall, our study demonstrated that ATM-AVI represents an important therapeutic option for infections caused by Enterobacterales, including key resistance phenotypes across different wards and infection sources.